2009
DOI: 10.1111/j.1348-0421.2009.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Archetype JC virus efficiently propagates in kidney‐derived cells stably expressing HIV‐1 Tat

Abstract: List of Abbreviations:AIDS, acquired immunodeficiency syndrome; BKV, BK virus; BKVAN, BK virus-associated nephropathy; CPE, cytopathic effect; DAB, 3,3 -diaminobenzidine tetrahydrochloride; FBS, fetal bovine serum; HA, hemagglutination; HIV-1, human immunodeficiency virus-1; JCV, JC virus; LTR, long terminal repeat; luc, luciferase; MEM, minimum essential medium; PBS, phosphate-buffered saline; PCR, polymerase chain reaction; pLTR-luc, HIV-1 LTR-dependent reporter gene; PML, progressive multifocal leukoencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…This is consistent with previous results showing replication of JCPyV DNA initiated by SV40 TAg is better than that of BKPyV DNA (Mahon et al, 2009). Archetype JCPyV DNA can replicate but not efficiently produce virus in POJ cells and COS-7 cells overexpressing JCPyV and SV40 TAg, respectively (Daniel et al, 1996; Hara et al, 1998; Nukuzuma et al, 2009). The difference in progeny production of archetype JCPyV from COS-7 cells compared to 293TT cells likely has to do with the very high levels of SV40 TAg produced in 293TT cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous results showing replication of JCPyV DNA initiated by SV40 TAg is better than that of BKPyV DNA (Mahon et al, 2009). Archetype JCPyV DNA can replicate but not efficiently produce virus in POJ cells and COS-7 cells overexpressing JCPyV and SV40 TAg, respectively (Daniel et al, 1996; Hara et al, 1998; Nukuzuma et al, 2009). The difference in progeny production of archetype JCPyV from COS-7 cells compared to 293TT cells likely has to do with the very high levels of SV40 TAg produced in 293TT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Archetype JCPyV DNA replicates in COS-7, simian kidney cells expressing SV40 TAg, and COS-7 cells expressing HIV-1 Tat (Hara et al, 1998; Nukuzuma et al, 2009). However, these systems show weak progeny production, taking up to 32 days to produce JCPyV as detected by hemagglutination assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Archetype JCV, which normally cannot be efficiently propagated in cell culture, can replicate in cells expressing HIV tat (369,370). tat has also been shown to be secreted from infected cells and internalized by uninfected cells, affecting cellular function (137,138,203,491,531) and thereby abrogating the necessity of JCV and HIV coinfection for the molecular interaction between these viruses.…”
Section: Pml and Hiv/aidsmentioning
confidence: 99%
“…A previous report has shown that Tat protein enhances the expression of the late promoter-dependent reporter gene of JCV in glial cells significantly [Tada et al, 1990]. Recently, it has also been shown that archetypal and PML-type JCV propagates efficiently in kidney-derived cells stably expressing Tat protein [Nukuzuma et al, 2009b;Nukuzuma et al, 2010].…”
Section: Introductionmentioning
confidence: 96%